Noteworthy idiosyncrasies of 1α, 25‐dihydroxyvitamin D3 kinetics for extrapolation from mouse to man: Commentary. (21st April 2020) - Noh, Keumhan; Yang, Qi Joy; Sekhon, Lavtej; Quach, Holly P.; Chow, Edwin C.Y.; Pang, K. Sandy
Abstract: Calcitriol or 1, 25‐dihydroxyvitamin D3 [1, 25(OH)2 D3 ] is the active ligand of the vitamin D receptor (VDR) that plays a vital role in health and disease. Vitamin D is converted to the relatively inactive metabolite, 25‐hydroxyvitamin D3 [25(OH)D3 ], by CYP27A1 and CYP2R1 in the liver, then to 1, 25(OH)2 D3 by a specific, mitochondrial enzyme, CYP27B1 (1α‐hydroxylase) that is present primarily in the kidney. The degradation of both metabolites is mostly carried out by the more ubiquitous mitochondrial enzyme, CYP24A1. Despite the fact that calcitriol inhibits its formation and degradation, allometric scaling revealed strong interspecies correlation of the net calcitriol clearance (CL estimated from dose/AUC∞ ), production rate (PR), and basal, plasma calcitriol concentration with body weight (BW). PBPK‐PD (physiologically based pharmacokinetic‐pharmacodynamic) modeling confirmed the dynamic interactions between calcitriol and Cyp27b1/Cyp24a1 on the decrease in the PR and increase in CL in mice. Close scrutiny of the literature revealed that basal levels of calcitriol had not been taken into consideration for estimating the correct AUC∞ and CL after exogenous calcitriol dosing in both animals and humans, leading to an overestimation of AUC∞ and underestimation of the plasma CL. In humans, CL was decreased in chronic kidney disease but increased in cancer. Collectively, careful pharmacokinetic data analysis and improved definition are achieved with PBPK‐PD modeling, which embellishes the complexity of dose, enzyme regulation, and disease conditions. Allometric scaling and PBPK‐PD modeling were applied successfully to extend the PBPK model to predict calcitriol kinetics in cancer patients.